2021
DOI: 10.1021/jasms.1c00053
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Efficiency Improvement to an Electrospray Ionization Mass Spectrometer and Its Implications for Liquid Chromatography Based Inlet Systems in the Nanoliter to Milliliter per Minute Flow Range

Abstract: This paper describes electrospray sampling efficiency measurements obtained on a triple quadrupole mass spectrometer equipped with a large atmosphere to vacuum sampling aperture and modified ion optics designed to confine the ions traveling in the intense expanding gas beam and prevent scattering losses in the entrance optics of the mass analyzer. Sampling efficiency, defined as the ratio of the number of ions captured in the first vacuum stage of the entrance optics to the number of analyte molecules entering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These results are consistent with previous publications that have mapped the electrospray sampling efficiency as a function of liquid flow rate for the same amount of injected sample. For instance, Schneider and coauthors found approximately 3-fold sampling efficiency difference when comparing flow rates of 100 μl/min and 5 μl/min for reserpine ions . Therefore, the actual reduction in the intensity of the signal in the OPI caused by the dilution is relatively small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous publications that have mapped the electrospray sampling efficiency as a function of liquid flow rate for the same amount of injected sample. For instance, Schneider and coauthors found approximately 3-fold sampling efficiency difference when comparing flow rates of 100 μl/min and 5 μl/min for reserpine ions . Therefore, the actual reduction in the intensity of the signal in the OPI caused by the dilution is relatively small.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Schneider and coauthors found approximately 3-fold sampling efficiency difference when comparing flow rates of 100 μl/min and 5 μl/min for reserpine ions. 57 Therefore, the actual reduction in the intensity of the signal in the OPI caused by the dilution is relatively small. However, by operation with a high dilution rate, the effects of ion suppression can be reduced or eliminated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…16,17 The novel dodecapole ion guide device called "Djet" could increase ion transfer efficiency from the ion source using a larger inlet orifice, and scatter losses in the shock waves of the accelerating gas are minimized to yield a signal improvement. 16,18 The stacked ring ion guide (SRIG) has advantages in trapping ions because of pseudopotential well scales as e r . 19,20 The SRIG, the ion tunnel, 21,22 and the S-lens 23 were used to improve ion transport efficiency in the first vacuum of commercial MS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This study described increasing the MS orifice and used a 150 mm long radio frequency quadrupole (RFQ) ion guide in an ∼10-fold elevated bulk gas pressure to deliver ions into the mass analyzer with good transfer efficiency. Many studies were published to improve the sensitivity by using RF ion guides with acceptance radius which could entrain a spatially dispersed ion cloud, such as quadrupole, , sextupole, , octupole, and dodecapole. , The novel dodecapole ion guide device called “Djet” could increase ion transfer efficiency from the ion source using a larger inlet orifice, and scatter losses in the shock waves of the accelerating gas are minimized to yield a signal improvement. , The stacked ring ion guide (SRIG) has advantages in trapping ions because of pseudopotential well scales as e r . , The SRIG, the ion tunnel, , and the S-lens were used to improve ion transport efficiency in the first vacuum of commercial MS. In contrast to a conjoined stepped RF ion guide, the electrodynamic ion funnel (EDIF) included a single stack of annular lenses and had the same achievement in ion transfer …”
Section: Introductionmentioning
confidence: 99%